Efficacy of Low-Dose rhGM-CSF Treatment in a Patient With Severe Congenital Neutropenia Due to CSF3R Deficiency: Case Report of a Novel Biallelic CSF3R Mutation and Literature Review - Zhou, Junli; Sun, Chengjun; Huang, Honglin; Zhu, Qiguo; Wen, Fengyun; Dong, Ying; Wang, Hongsheng (Frontiers in Pediatrics, 2021)
The study reported the clinical manifestations and genetics of a patient with severe congenital neutropenia (SCN) casued by novel biallelic mutations in CSF3R, and the efficacy of the recombinant human granulocyte macrophage colony-stimulating factor (rhGM-CSF). The chart of a child with SCN were analyzed retrospectively. Genetic diagnosis was performed by whole exome sequencing (WES) and Sanger sequencing. The relationship between neutropenia and CSF3R gene was studied by rtPCR and Western blot using peripheral blood from the family. Treatment using rhGM-CSF and follow-up was reported. The proband was a 2-year-old girl who had recurrent suppurative tonsillitis, along with decreased absolute neutrophils count (ANC) < 0.5×109/L. WES and Sanger sequencing detected two novel heterozygous mutations inherited from each parent (maternal c.690delC [p.met231Cysfs*32] and paternal c.64+5G>A). The expression of CSF3R protein in children was significantly lower than that of their parents. Low dose rhGM-CSF (3 μg/kg/day once a week) is capable of maintaining our patient from recurrent infection. The patient’s treatment results suggested that the clinical manifestations of SCN7 with biallelic CSF3R mutations and decreased CSF3R could be effectively treated by rhGM-CSF to increasing neutrophils and resolve repeated infection.